Labour Migration in Europe Volume II Exploitation and Legal Protection of Migrant Workers (Springer International Publishing, 2018)
Violence, deception, fraud and abuse have always been commonplace occurrences for migrants, not only in their final country of destination but also in their countries of origin and countries of transit. In today's world, the link between mobility and security issues is ever-increasing. Acknowledging this, how can we work to protect and improve migrants' rights? Is the protection for migrants offered by the EU sufficient as-is, or is a more integrated approach that requires greater cooperation from migrants' country of origin called for? What role can the private sector play in all of this? In this book, Borraccetti brings together contributions that analyse how migrant exploitation can be combatted. All essays focus on the protection and promotion of human rights and pay particular attention to the rights of children and other vulnerable people. Marco Borraccetti is Researcher and Senior Lecturer of European Union Law at the University of Bologna, Italy, where he teaches the Jean Monnet Module EU Law and EU Immigration Law. His research interests include migration, human-trafficking and the judicial protection of fundamental rights in the EU. .